Evaluation and appraisal of drug information services in a rural secondary level care hospital, Anantapur, AP - Rohit Bhavsar; Seeba Zachariah; Dixon Thomas; Shanmugha M Kannan (Wolters Kluwer Medknow Publications, 2012)
Background: Drug Information Center (DIC) is an information center which provides drug information (DI) to healthcare professionals. The aim was to evaluate the performance of DIC for improving the quality and quantity of information services provided to the healthcare professionals. The service was provided free of cost to the customers. Materials and Methods: This descriptive study was conducted for the period of 6 months from February to August 2011 excluding May due to vacation. Customers were asked: how did they find the service provided to them? Was it good, satisfactory, or need improvement? There were written feedback forms to be filled by the customers, including customer satisfaction questions. The official publication of the DIC, RIPER PDIC Bulletin was screened for its types of articles/number of drug news published. The bulletin is circulated for free to the healthcare professionals electronically. Results and Discussion: A total of 232 queries were obtained during the study period of 6 months. Average number of queried received to the DIC was 39 per month. Most preferred mode of queries was personal access (89%). Majority of queries were received from nurses, i.e., 162 (70%) queries and 81% of all queries were drug oriented for improving knowledge. There were only 19% of the queries for individual patients; doctors asked most of those queries. Only 3% queries answered were rated as need improvement by the healthcare professionals. Rest were considered as either Good (56%) or satisfactory (49%). Range of drug news published in each bulletin was 3-4 and most of the other articles include expert opinion to improve practice or training. Conclusion: The DI services were satisfactorily used for academic interests. Nurses used the service for the highest compared to other health care professionals. Future studies should plan to establish the usefulness of DI to improve healthcare practice.